Alcala, Victoria, Susana Thénon. Loba esteparia, Buenos Aires, Ediciones Lamas Médula, 2020, 164 pp. - Tamai, Agustín Francisco (2020)
Fil: Tamai, Agustín Francisco. Pontificia Universidad Católica Argentina; Argentina